Le mandat apparent en droit public - Lemieux, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
A public servant's scope of authority is determined by law and not, as recent decisions would appear to say, by any notion of « apparent authority », or « apparent mandate ». Indeed, the theory of « apparent mandate », which deals only with the granting of legal capacity, does not apply on the face of legislative or statutory provisions to the contrary.